Církev a homosexualita: Normativní pojetí a osobní koncepty u křesťanských duchovních - Koumar, Jan (Lidé města, 2012)
This material deals with the personal concepts of homosexuality that the clergymen of Christian churches create as a reaction to the normative approach of their church and as a reaction to social reality. The material contains the description, data and the results of the research I conducted among homosexual clergymen in the Czech Republic, and it originally constituted the practical part of the bachelor's thesis I wrote under the tutelage of M. C. Putna at the Faculty of Humanities at Charles University in Prague. The questions this research set out to answer were how Christian clergymen regard homosexuality, how they understand the normative approach of their own church and how much they agree with it, and furthermore, to what extent they are "out of the closet" and to what extent they fit into the normative view of their church.